Evaluation of Epithelial Mesenchymal Transition Markers E-Cadherin and Vimentin in Carcinoma Cervix - R, Naveen Kumar; Ahluwalia, Charanjeet; Malik, Sunita; Arora, Rashmi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Cervical cancer is the second most common in developing areas. Epithelial to mesenchymal transformation, one of the critical elements in invasion, progression and metastasis of tumour. This study highlights the expression of epithelial mesenchymal markers E-cadherin and vimentin in carcinoma cervix and whether there is any association of expression of these markers with grade of cervical cancer. Objectives: To study the expression of epithelial mesenchymal transition (EMT) markers E-cadherin and vimentin in cervical cancer. To correlate the immunohistochemical expression of these markers with grade of cervical cancer. Methods: 30 cases (n=30) of carcinoma cervix & 30 controls (n=30) of non specific cervicitis diagnosed on H&E were included in this study. H&E stained sections was examined for histological type and grade. Immunohistochemistry for E-Cadherin and Vimentin was performed in all these cases. Result: Immunohistochemical expression of epithelial marker E-cadherin and of mesenchymal marker vimentin was correlated with the grade of cervical carcinoma. The expression of E-cadherin is reduced and expression of vimentin is increased with increasing grades of carcinoma cervix. Conclusion: The expression of these EMT markers can be used as a prognostic marker in cervical cancer that are in high risk of progression.